Integration of Hadith Values in Psychotherapy: Efforts to Build Mental Health Based on Islamic Spirituality: Penelitian - Irfan Padlian Syah; Ahmad Furqon Al Mubarok (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to find out the expression of the hadith about psychotherapy and find out what psychotherapy was taught by the Prophet. This research adopts a thematic method in analyzing contemporary hadiths, as well as applying theories developed from data through a grounded theory approach. Islamic psychotherapy is the process of healing and handling various diseases, both mental, spiritual, moral, and physical, which is carried out based on the instructions of the Qur'an and the Sunnah of the Prophet. The therapy taught by the Prophet is full of wisdom and benefits. This therapy is not only effective for curing liver disease, but it can also address physical problems. The peculiarity of the Prophet's therapy lies in the fact that it does not require large costs, but only requires knowledge and is done consistently to experience extraordinary results. Some of the therapeutic models carried out by the Prophet include: ablution, prayer, fasting, zakat/alms, hajj, istighfar, and prayer, and perhaps many other therapies taught by the Prophet.